Hak Cuti Melahirkan dan Perlindungan Pekerja Wanita dalam Perspektif Hukum Ketenagakerjaan - Vannya Anastasya (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
Although female workers play a vital role in economic growth, they also face challenges related to their reproductive health, particularly regarding maternity leave rights. Using a normative-legal methodology, this study aims to examine how Indonesian labor law regulates and implements maternity leave rights. The study considers both legal and conceptual aspects. This study shows that Indonesia has a strong, binding, and protective legal framework based on the 1945 Constitution and Law No. 13 of 2003. However, in real life, problems such as discrimination, wage reductions, and even termination of employment still exist. This is exacerbated by a lack of oversight and legal awareness. In conclusion, this study recommends enhancing maternity leave protections by combining regulations with improved oversight to provide fairer and more efficient protection for female workers.